Exploring the physicochemical and microbiological properties of glutinous rice (Tapai pulut) fermented using Lactobacillus plantarum: A comprehensive characterization using 1H NMR - Anzian, Aliaa; Hussin, Muhaini; Qadir, Rahman; Azhari, Siti Hajar; Juhari, Nurul Hanisah; Yusof, Yus Aniza; Adnan, Hazniza; Meor Hussin, Anis Shobirin (Elsevier Ltd, 2024)
This study aimed to investigate the potential of producing lacto-fermented glutinous rice (Tapai pulut) to improve its physicochemical properties, metabolite compounds, and antibacterial activity of the end product. Glutinous rice was fermented with Amylomyces rouxii, and Lactobacillus plantarum 1 at 30 °C for 48 h. Lacto-fermented glutinous rice had significantly lower pH values and higher total lactic acid, soluble solid, glucose, and organic acid contents. The 1H NMR metabolomics profile revealed the presence of alcohols (7.67 mmol/L), sugars (208.16 mmol/L), organic acids (0.91 mmol/L) and amino acids (15.74 mmol/L), contributing to its antimicrobial activities and flavor profile. The lacto-fermented glutinous rice exhibited strong antibacterial activity against Bacillus cereus (18.20 mm), Staphylococcus aureus (18.92 mm), Listeria monocytogenes (15.42 mm), Escherichia coli (15.85 mm), and Salmonella typhimurium (12.23 mm). Meanwhile, the viable count of lactic acid bacteria (LAB) in the lacto-fermented glutinous rice was 9.49 log10 CFU/g. Based on sensory evaluation and positive feedback from panelists, lacto-fermented glutinous rice emerges as a promising probiotic food with potential health benefits for consumers.